A PROSPECTIVE STUDY FOR THE EVALUATION OF NERVE CONDUCTION ABNORMALITIES IN NEWLY DIAGNOSED TYPE 2 DIABETIC PATIENTS - GOVINDARAJU, LORD KRISHNA; VADIVEL, KAMALAKANNAN; TALIKOTI, PRASHANTH; T, RAVI KUMAR; D, JEYALAKSHMI; PRABHU V, VENGADESH (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Peripheral neuropathy is the one of the frequently encountered complication of type 2 diabetes mellitus (T2DM). Although, the prevalence of diabetic peripheral neuropathy is associated with the diabetes duration, in some cases, the state of neuropathy is evident at the time of diagnosis. In this backdrop, the present study was carried out to evaluate the nerve conduction abnormalities in newly diagnosed T2DM. Methods: This was a prospective study carried out on 30 newly diagnosed T2DM within a time range of 1 month. The patient symptoms such as weakness, burning and tingling senzation, hyperesthesia, and foot ulcer and gait abnormalities were recorded. Nerve conduction analysis of upper limb and lower limb of non-dominant hand side was done using neuro pack S1 machine. Results: Thirty newly diagnosed T2DM patients were enrolled in the present study. The mean age of the patients was found to be 58.12±15.28 years. Distal motor latencies were elevated in T2DM patients as compared to the controls (p<0.05). Further, there was significant prolongation of F-wave latencies in the upper and Lower limbs of the patients as compared to the controls (p<0.05). In addition, there was a significant decrease in sensory conduction velocities in T2DM patients as that of the controls (p<0.05). Conclusion: The study concludes that newly diagnosed T2DM is susceptible to DPN with high incidence rates. Hence, it is essential to perform the nerve conduction studies in newly diagnosed T2DM patients for the early detection and better management and also to prevent the complications.